Status, trends and future scenarios for forest conservation including protected areas in the Asia-Pacific region - Paine, J. R.; Byron, R.N.; Poffenberger, M. (Food and Agriculture Organization of the United Nations, 1997)
This paper attempts to assesses future prospects for forest conservation, especially protected areas, in the Asia-Pacific region to the year 2010, under three scenarios assuming: - continuation of the present level of action and policy environment ('status quo'); - sustained environmental campaigns and a heightened role for conservation than exists at present; and - negative changes in policy and action related to conservation. Local people will permit forests to remain if they believe that the forests' continued existence is more beneficial (e.g., generates higher incomes or has cultural or social values) than their removal. If not, forests are cleared. Official conservation policies of forestry agencies may be irrelevant, or even directly contradicted, by policies outside the forestry sector. The conservation of biodiversity and deforestation can thus only be resolved by considering the problems of forest-dependent communities in a wider context, such as population movements, and access to land. Many Asian countries are thus in the process of formulating policies that provide for communities' involvement in managing public conservation forests. These new collaborative approaches, while widely supported by donor organisations, are still imperfect. Only a very small percentage of the public forest estate of Asia has been formally brought under co-management. For decades communities have been viewed as a threat to forest biodiversity and commercial production. Bringing communities formally into management and devolving authority and rights to them is a dramatic shift of direction. The process of negotiating conservation management agreements between communities, forest departments, and local governments is formidable Politically disempowered communities and women need effective representation as new forest management agreements are formulated for conservation.